PENGARUH SOCIAL MEDIA MARKETING, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOKO ASIA BARU CAKE & BAKERY KENDARI - Sardi, Wisnu Tri; Adinansyah, Rafly (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is: (1) Determine the influence of social media marketing on purchase decisions at Asia Baru Cake & Bakery Kendari. (2) Determine the influence of price on purchase decisions at Asia Baru Cake & Bakery Kendari. (3) Determine the influence of product quality on purchase decisions at Asia Baru Cake & Bakery Kendari. This research is categorized as quantitative, with the consumers of Asia Baru Cake & Bakery in Kendari as the primary population. A total of 96 individuals were selected as the sample using a non-probability sampling approach, specifically employing purposive sampling. The data collection instrument was a Google Form-based questionnaire using a Likert Scale for measurement. The collected data was then analyzed using multiple linear regression. Based on the analysis results, it was found that social media marketing has a positive and significant impact on purchasing decisions. Similarly, price and product quality variables also show substantial positive effects on purchasing decisions. When tested simultaneously, the three variables—social media marketing, price, and product quality—significantly influence consumers' purchasing decisions.